Aktivitas Antioksidan Ekstrak Daun Jambu Biji (Psidium guajava L.) - Susi Indriani (Institut Pertanian Bogor, 2006)
Antioxidant has an important role in healing some kind of dieses caused by excessive oxidation reactions in human body. That leaf has benefit to resist diarrhea, anti inflammation, and anti mutagenic. It is assumed it could be used as antioxidant. The research was aimed to know the antioxidant activity of the extract of Psidium guajava leaf. The local leaf was from Bantar Kambing area in Bogor. The methods were thiocyanate method and thiobarbituric acid (TBA) method. The result showed that the leaf wich had the best antioxidant potential was the white local Psidium guajava leaf extracted by ethanol 70% in a maceration manner. In the tyochianate method, the extract of white Psidium guajava leaf had protective factor near to Vitamin E or tocopherol, that is 1.10 and tocoferol was 1.16. antioxidative evaluation using the TBA method showed that the highest activity was from ethanol extract of white Psidium guajava leaf could obstruct it up to 94.19% toward the control, however the actif constituents are unknown. Phytochemical evaluation result showed that the Psidium guajava leaf are contained tannin, phenol, flavonoid, quinon, and steroid.